Evaluation of epididymal and frozen sperm to produce goat embryos through in vitro fertilization - AbdElkhalek, A. S.; Ghanem, N.; Soliman, M. G.; Abu El Naga, N. A.; Kamel, A. M.; Shedeed, H. A.; El Bahrawy, K. A. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
Preservation of the livestock genetic makeup could be performed by application of in vitro fertilization (IVF) using spermatozoa collected from cauda epididymis. Therefore, this study as sessed the development of goat embryos following IVF of spermatozoa collected from cauda epididy mis compared to those kept frozen. Oocytes were in vitro cultured in a maturation medium for 24 hours at a temperature of 38.5°C, 5% CO2, and 95% humidity. Following maturation, the oocytes (n = 370) were in vitro fertilized by fresh epididymal sperm (G1) and G2 frozen-thawed sperm, and the Fert-TALP medium was used as the IVF medium. In addition, in vitro developed embryos were cultured in GT-L medium. The fertilization rate, percentage of morula, and blastocytes (p<0.01) were significantly higher in oocytes inseminated with epididymal than in frozen sperm. In conclusion, in vitro embryo production of goat oocytes may be successfully performed using epididymal spermatozoa for IVF.